Measuring the Literacy and Understanding Skills of Makassar Students in Using Artificial Intelligence-Based Applications - Muhammad Ashraf Naim S; Ahmad Aiman Sanjaya; Rian Irham Putra; Mulky Subhan; Passalowongi, Irfan Jamal; Wahyu Hidayat M (Jurnal MEKOM (Media Komunikasi Pendidikan Kejuruan), 2025)
In the era of the Industrial Revolution 4.0, the use of technology has become increasingly widespread and impacted various aspects of life, including education. One such technology that is increasingly developing is artificial intelligence (AI). This study focuses on students' perceptions of measuring Makassar students' literacy skills in using AI-based applications. This study includes an evaluation of students' literacy skills in the context of using artificial intelligence (AI)-based applications. By using questionnaires or assessment instruments, this study will measure the extent to which students understand and are able to apply their knowledge related to AI technology. This study uses a quantitative methodology, namely distributing questionnaires or surveys to determine the level of validity. This study produces data from surveys conducted to a number of respondents. The assessment was carried out to determine how deep the literacy skills and understanding of Makassar students are in using AI-based applications. Based on the results of this study, students in Makassar responded positively to the use of AI Literacy. They assessed AI Literacy as effective in supporting learning and work, providing useful solutions, and understanding user needs. The responsiveness of AI Literacy was highly rated, with students considering it effective and easy to use. This positive impact on students included an improved learning experience.